The Implementation of Baamboozle Website for Teaching English Vocabulary to ‘Aisiyah Singopuran Kindergarten - Diah Fajar Rahmawati; Hepy Adityarini (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study aims to examine the implementation of the Baamboozle website as a game-based learning medium for teaching English vocabulary to kindergarten students, to explore the teacher’s perception of its use, and to analyze students’ responses toward Baamboozle-based learning. In early childhood education, English vocabulary instruction requires interactive and engaging approaches that align with young learners’ cognitive characteristics and learning preferences, making the integration of digital game-based tools increasingly relevant in Teaching English to Young Learners (TEYL). This research employed a descriptive qualitative approach with a case study design conducted at TK ‘Aisiyah Singopuran, involving one English teacher and eleven senior-class kindergarten students. Data were collected through classroom observations to investigate the learning implementation and students’ responses, as well as semi-structured interviews to capture the teacher’s perception of using Baamboozle. The findings reveal that Baamboozle was implemented effectively through structured stages, including student grouping, explanation of game rules, and vocabulary learning activities, which created an interactive and enjoyable learning atmosphere. The use of Baamboozle increased students’ engagement, motivation, and vocabulary retention, while encouraging collaboration among learners. The teacher perceived Baamboozle as an effective and accessible learning medium that supports both classroom and home-based learning, although limited free game features were identified as a minor challenge. Overall, students responded positively to Baamboozle-based learning, demonstrating high enthusiasm and active participation. The study concludes that Baamboozle is a suitable and effective digital tool for supporting English vocabulary learning in kindergarten contexts.